পাহাড়ি মিডিয়া : বাস্তবতা এবং আত্ননির্মাণ - খোন্দকার, শাহিদা ইসলাম; প্রিয়দর্শিনী, আনমনা; BRAC University. Development Institute; Pathways of Women's Empowerment Programme (ঢাকা : BRAC Development Institute (BDI), 2011)
Study on the role and importance of mass media in the life of women in Chittagong Hill Tracts region of Bangladesh, based on Pathways of Women's Empowerment Programme.
Includes bibliographical references (page 28).
AAL
Complementary copy
In Bengali.
Keywords: Mass media and women -- Bangladesh -- Chittagong Hill Tracts (Region); Mass media and women; Bangladesh -- Chittagong Hill Tracts (Region)